2015
DOI: 10.1039/c4ta06857b
|View full text |Cite
|
Sign up to set email alerts
|

Formation of bilayer clathrate hydrates

Abstract: We report molecular dynamics (MD) simulation evidence of a new family of two-dimensional (2D) clathrate hydrates. Particular attention is placed on the effect of size and hydrophilicity of guest-molecule on the formation of 2D clathrate hydrates.Among MD simulations undertaken, spontaneous formation of bilayer (BL) clathrate hydrates in nanoslits are found with five different hydrophobic guest molecules, namely, ethane (C 2 H 6 ), ethene (C 2 H 4 ), allene (C 3 H 4 ), carbon dioxide (CO 2 ) and hydrogen (H 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…However, when the pore size is reduced to subnanometer, the hydrogen-bonding network in water is disrupted by the highly confined environment, thereby affecting the kinetics of crystallization. In 2D nanoconfinement, monolayer or bilayer gas clathrates can be formed under thousands of atmospheric pressures, ,, while quasi-one-dimensional (Q1D) core–sheath n -gonal ( n = 5–8) hydrogen hydrates can be formed spontaneously within single-walled carbon nanotubes (SW-CNTs) . Also, the formation of Q1D heptagonal and octagonal hydrogen hydrates can be seen under ambient pressure when the SW-CNTs are immersed in the dilute H 2 aqueous solution …”
mentioning
confidence: 99%
“…However, when the pore size is reduced to subnanometer, the hydrogen-bonding network in water is disrupted by the highly confined environment, thereby affecting the kinetics of crystallization. In 2D nanoconfinement, monolayer or bilayer gas clathrates can be formed under thousands of atmospheric pressures, ,, while quasi-one-dimensional (Q1D) core–sheath n -gonal ( n = 5–8) hydrogen hydrates can be formed spontaneously within single-walled carbon nanotubes (SW-CNTs) . Also, the formation of Q1D heptagonal and octagonal hydrogen hydrates can be seen under ambient pressure when the SW-CNTs are immersed in the dilute H 2 aqueous solution …”
mentioning
confidence: 99%
“…Thus, it is necessary to study the interaction between gas and water in the organic nanochannels (Li et al, 2016(Li et al, , 2017aShen et al, 2019). Although the phase change, the occurrence state and the flow mechanism of water/gas molecules in nanopores have been the research hotspots in natural science and many engineering fields (Hummer et al, 2001;Dammer and Lohse, 2006;Bai and Zeng, 2012;Zhao et al, 2014bZhao et al, , 2015Kou et al, 2015;Lee and Aluru, 2015;Wang et al, 2016;Li et al, 2019aLi et al, , 2019b. In view of the particularity of shale pore structure and reservoir property, the research on gas in confined space in petroleum engineering field is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…To clear formation mechanism of hydrate containing hydrogen, some calculations and experiments were ever carried out from the microscopic point of view. Zhao et al [37] reported that guest molecules with various size and hydrophilicity presented different characteristics when they were participating in the process of hydrate formation in microscopic media. Moreover, Raman shift changed involving into guest-host hydrogen bonding, according to the results reported by Lim et al [38] in the system with diazine isomers.…”
Section: Introductionmentioning
confidence: 99%